2022
DOI: 10.1093/oncolo/oyab011
|View full text |Cite
|
Sign up to set email alerts
|

Toripalimab Plus Paclitaxel and Carboplatin as Neoadjuvant Therapy in Locally Advanced Resectable Esophageal Squamous Cell Carcinoma

Abstract: Introduction Immune checkpoint inhibitors (ICIs) are effective in the treatment of advanced esophageal squamous cell carcinoma (ESCC); however, their efficacy in locally advanced resectable ESCC and the potential predictive biomarkers have limited data. Methods In this study, locally advanced resectable ESCC patients were enrolled and received neoadjuvant toripalimab (240 mg, day 1) plus paclitaxel (135 mg/m2, day 1) and carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 53 publications
2
87
0
Order By: Relevance
“…It had been reported that TPS had a better prediction performance than CPS in EC ( 21 ). Moreover, PD-L1 expression can be upregulated by CT/CRT in patients with EC ( 38 , 48 , 49 ). In a phase 2 trial of EC ( 38 ), there were 5 patients (29%) whose CPS changed from 0 before nICT to ≥ 1 after nICT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It had been reported that TPS had a better prediction performance than CPS in EC ( 21 ). Moreover, PD-L1 expression can be upregulated by CT/CRT in patients with EC ( 38 , 48 , 49 ). In a phase 2 trial of EC ( 38 ), there were 5 patients (29%) whose CPS changed from 0 before nICT to ≥ 1 after nICT.…”
Section: Discussionmentioning
confidence: 99%
“…The selection process and reasons for study exclusion are shown in Figure 1. Among the 27 studies, 8 trials with 221 patients examined nICRT (14-21), 19 trials with 588 patients examined nICT (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Except one twoarms trial (33), all included studies were single-arm trials.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…Of the 21 studies included, there were 20 single-arm open-label cohort studies ( 15 , 19 37 ) and there was one two-arm open-label randomized controlled trial (RCT) ( 38 ). Of the 21 studies included, three are still ongoing ( 26 , 29 , 30 ) and 18 ( 15 , 19 25 , 27 , 28 , 31 38 ) have been completed. The main neoadjuvant immunotherapy drugs include pembrolizumab, sintilimab, and camrelizumab, amongst others.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve of the 21 studies achieved 100% R0 resection, with an overall mean R0 resection rate of 97.5%. The remaining nine studies ( 15 , 19 , 23 25 , 27 , 32 , 36 , 37 ) had individual ORs as well as combined ORs <1 (OR=0.95,95% CI: 0.90–1.00, p <0.001; Figure 5 ). Heterogeneity ( p <0.001, I 2 = 94%) was significant, so a random-effects model was used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation